Revitalization of Ijarah Agreements in Islamic Banking Service Products - Khulwah, Juhrotul (Advances In Social Humanities Research, 2024)
The revitalization of the ijarah contract is urgently needed by the community so that the community not only uses the classic ijarah contract in daily life but can use the ijarah contract that has been revitalized in modern times, such as the muntahiyah bi al-tamlik ijarah contract and multi-service ijarah contract, so that more service products can be produced from the ijarah contract, and can make the community more empowered by the continuous development of the times. This study aims to explain ijarah contracts that have undergone revitalization so that they can be used more by the community, to develop the service products used. So the problem in this study is "What are the forms of the revitalization of ijarah contracts in Islamic banking service products." To find the answer to this question, the research method uses qualitative research, the type of research library research, and the nature of analytical descriptive research. The findings in this study are that there has been a revitalization of ijarah contracts in service products in Islamic banking, such as ijarah muntahiyah bi al tamlik and multi-service ijarah contracts. If this contract is maximized both in products and their use, it will be very profitable and convenient to get, both from the service provider and the community.